9514 1404 393
Answer:
a ≈ 4.68
Step-by-step explanation:
The law of cosines tells you ...
a² = b² +c² -2bc·cos(A)
a = √(b² +c² -2bc·cos(A))
a = √(5² +8² -2·5·8·cos(33°)) = √(25 +64 -80·0.83867) ≈ √21.906
a ≈ 4.68
Your answer is A. You literally plug in the numbers for a and b to solve for the equation.
Answer:
Bill received 13.68 change back.
Step-by-step explanation:
20-6.32=13.68
The square on the hypotenuse is skew and impossible to visually validate. There's nothing to sum. It is a simple calculation to note that <span><span><span>32</span>+<span>42</span>=<span>52</span></span><span><span>32</span>+<span>42</span>=<span>52</span></span></span><span>, but its picture doesn't 'say' that the angle between the 3 and 4 sided square must be 90 degrees.
</span>
Answer:
$24
Step-by-step explanation:
1/4x + 1/3x + 8 = 22
1/4x + 1/3x = 7/12x
7/12x + 8 = 22
22 - 8 = 14
7/12x = 14
14/ 7/12
x = 24